Synthesis, docking studies, biological activity of carbon monoxide release molecules based on coumarin derivatives - Liu, Huapeng; Chen, Yujie; Cui, Fujun; Liao, Yuan; Wang, Xicun (Frontiers in Chemistry, 2022)
In the present work, we synthesized seven complexes. All complexes were identified by ESI-HRMS, 1H-NMR, 19F-NMR and 13C-NMR spectroscopies. The synthesized complexes were tested for their anticancer activities in vitro against three different human cell lines, including breast MDAMB231, cervical Hela, liver HepG2. IC50 values of complexes 1-7 were 34.98-667.35 µM. Complex 5 revealed higher sensitivity towards MDAMB231 cells with IC50 values 34.98 μM in comparison to 5-FU as positive control. Moreover, complex 5 caused a decrease of mitochondrial membrane potential and effectively induced ROS production against MDAMB231 cells. Western blot analysis showed that complex 5 could up-regulate the expression of Bax protein and down-regulate the expression of Bcl-2, activate Caspase-3, slightly down-regulate the expression of HO-1. The docking studies showed that complex 5 could be interacted with Bcl-2 protein through hydrophobic interactions, hydrogen bonds and salt bridges to enhance the binding affinity. All the analyzed coumarins obeyed the Lipinski’s rule of five for orally administered drugs. Based on the aforementioned results, it suggests that the complex induced apoptosis cell via mitochondria pathways. Collectively, complex 5 could be considered as a promising hit for new anti-breast cancer agents. Carbonyl cobalt CORMs, as potential anticancer therapeutic agents, provided a new idea for the development of metal anticancer drugs.